If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9(x+2)+3x+5=5x+10
We move all terms to the left:
-9(x+2)+3x+5-(5x+10)=0
We add all the numbers together, and all the variables
3x-9(x+2)-(5x+10)+5=0
We multiply parentheses
3x-9x-(5x+10)-18+5=0
We get rid of parentheses
3x-9x-5x-10-18+5=0
We add all the numbers together, and all the variables
-11x-23=0
We move all terms containing x to the left, all other terms to the right
-11x=23
x=23/-11
x=-2+1/11
| (3x+4)+(6x-4)=0 | | 7(2x-)=42 | | 7+13a=-99 | | X+0.2x=54 | | (4x-6)+(8x-6)=0 | | 3p+3(0.75)=5.88 | | X+0.2x=108 | | 8*s=1.25 | | 10-2(x+4)=22 | | y(2+3)=30 | | (4x-2)=(5x-4) | | 8^2r=32 | | (5x-4)+(4x-2)=0 | | 15.2-3.1x=4.7 | | -3g-5+2g=-4-g+9 | | 8x-(2x+2)=4x-38 | | (5x-4)+(4x-2)=180 | | 2/3(13)-8=x | | (x+12)+(4x-7)=180 | | 20+20x=40 | | 125=15(x-65)+50 | | 7(3x+4)-9(2x+3)=10 | | (x+12)=(4x-7)=180 | | 3y+14=-5(y+2) | | (7x+6)=(9x-24)=180 | | 3y-3=-(32-4y) | | -8x-4-3x+2=-13 | | 3y-3=32-4y | | 6z=0.36 | | 43=x+.1x | | 6x2=3x-5=0 | | 2(4x+1)=+5(x-3) |